T2 shading and T2 dark spot sign in the diagnosis of endometriotic cysts: A prospective study - Insha Khan; Anchal Gupta; Mohd Ilyas (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of the study is to assess the sensitivity and specificity of T2 shading and T2 dark spot sign in the diagnosis of endometriotic cysts. Materials and Methods: The present study evaluated adnexal hemorrhagic lesions without solid component investigated using sonography and 1.5 Tesla magnetic resonance imaging machine for the presence of T2 shading and T2 dark spot sign and their statistical value in the diagnosis of endometriotic cysts. The final study included 64 patients. Results: The T2 shading sign had the sensitivity and specificity of 85.71% and 37.5%, respectively. The T2 dark spot sign had the sensitivity and specificity of 76.79% and 100%, respectively. Conclusion: T2 shading sign is highly sensitive for the diagnosis of endometriotic cysts, whereas the T2 dark spot sign is highly specific for the diagnosis of endometriotic cysts. T2 shading sign has low specificity and T2 dark spot sign has low sensitivity.